A handbook to the reception of Thucydides - Lee, Christine M.; Morley, Neville (Chichester, West Sussex, UK : John Wiley & Sons Ltd, 2014)
A Handbook to the Reception of Thucydides offers an invaluable guide to the reception of Thucydides, with a strong emphasis on comparing and contrasting different traditions of reading and interpretation. Presents an in-depth, comprehensive overview of the reception of the Greek historian Thucydides Features personal reflections by eminent scholars on the significance and perennial importance of Thucydides' work Features an internationally renowned cast of contributors, including established academics as well as new voices in the field.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Thucydides -- Appreciation; Thucydides; Art appreciation; Historiography; HISTORY / Ancient / Greece; Literary criticism; Greece -- Historiography; Greece; Electronic books